In-Vitro Analysis of Polyethylene Liner Wear Performance at 3 and 5 Million Cycles - Shitong YAN; Jianjun WANG; Jian SU (Zhongguo yiliao qixie zazhi)
ObjectiveThe purpose of this study is to compare the wear properties of UHMWPE acetabular liners after undergoing 3 million (3 Mc) and 5 million (5 Mc) cycles of in-vitro wear testing. The results will serve as a reference for the design of in-vitro testing for hip prostheses and as a control for clinical revision removals. MethodsWear tests were conducted on three different sizes of acetabular liners (28 mm, 32 mm, and 36 mm internal diameters) using a hip simulator to determine the amount of wear after 3 and 5 million cycles. The analysis included the number, size, and shape of abrasive particles. ResultsAfter 3 and 5 million cycles of wear, the amount of wear on the acetabular liner increased as the inner diameter increased. The abrasive particles had an average equivalent circular area diameter (ECD) of 0.27 μm and 0.29 μm, and 94.4% and 90.1% of the aspect ratio (AR) less than 4. ConclusionThe amount of wear on the acetabular liner after 3 Mc wear can indicate the wear performance of the product. The number of particles increased and the percentage of fibrous particles was higher after 5 Mc wear compared to 3 Mc wear.